Measurement of electron number density and temperature of laser-induced Silver plasma - Musadiq, Muhammad; Iqbal, Munawar; Amin, Nasir; Jamil, Yasir; Naeem, M. Asif; Shahzad, Hafiz Akif (International Journal of Engineering and Technology, 2012)
Silver (Ag) plasma generated by second harmonics (532 nm) of a Nd:YAG laser has been investigated at 17.6 mJ and 88.6 mJ energy level. The excitation temperature was determined from the Boltzmann plot method of the transition (3D3 -3P2) at 243.779 nm, (2S1/2 - 2P3/2) at 328.068 nm, (2S1/2 - 2P1/2) at 338.289 nm, (2P1/2 - 2D3/2) at 520.907 nm and (2P3/2 - 2D5/2) at 546.550 nm, while the Stark broadening (SB) method was used to measure the Electron Number Density (END) of 2P3/2 - 2S1/2 transition at 827.351 nm. The spatial behavior of the Electron number density (END) and Electron Temperature (ET) was measured at ambient air pressures at different energy level and distance ranging form 0-4.5 mm form the target metal. The ET were found to be varies from 17895 K to 10593 K, while END was found to be in the ranges of 2.229 ´ 1015 to 6.44 ´ 1014 cm-3 and 1.76 ´ 1016 to 1.893 ´ 1015 cm-3 for 17.6 mJ and 88.6 mJ energy, respectively. The relationship of END and ET found directly related to laser irradiance, while they were inverse to the distance form the target material surface to laser beam source.